Communication practices for delivering health behaviour change conversations in primary care: a systematic review and thematic synthesis - Albury, C; Hall, A; Syed, A; Ziebland, S; Stokoe, E; Roberts, N; Webb, H; Aveyard, P (BioMed Central, 2019)
Background: Clinical guidelines exhort clinicians to encourage patients to improve their health behaviours. However, most offer little support on how to have these conversations in practice. Clinicians fear that health behaviour change talk will create interactional difficulties and discomfort for both clinician and patient. This review aims to identify how healthcare professionals can best communicate with patients about health behaviour change (HBC).